Intergenerational relations of junior schoolchildren (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the study of gender features anddifferences in the behavior of boys and girls. The goal of the work is tosystematize and analyze the behavior of children in situations of official andunofficial intergender communication. Through communication, the childlearns the world and himself in it, acquires social experience, develops andestablishes himself as a person. The most characteristic feature ofcommunication is the disclosure of the subjective world of one person foranother. This activity is extremely important for a child, who begins todiscover a complex and diverse world. The article presents the results of asociometric study aimed at studying the intergenerational communication ofjunior pupils.